A multiscale signalling network map of innate immune response in cancer reveals cell heterogeneity signatures - Maria Kondratova (Nature Portfolio, 2019)
The complexity of the innate immune response to cancer makes interpretation of large data sets challenging. Here, the authors provide an integrated multi-scale map of signalling networks representing the different immune cells and their interactions and show its utility for data interpretation.